PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII DI SMP NEGERI 2 BANGKINANG KOTA - Dedi Chandra; Adityawarman Hidayat; Astuti Astuti (Jurnal Dedikasi Pendidikan, 2024)
This research is motivated by the less than optimal mathematics learning process caused by mathematics learning that is fixated on the teacher. This study aims to determine the effect of the Realistic Mathematics Education learning approach on mathematics learning outcomes for class VII SMP Negeri 2 Bangkinang City. This research is an experimental research with a pretest posttest control group design model. The research subjects were seventh grade students of SMP Negeri 2 Bangkinang City. The sampling technique in this study was random sampling, consisting of 29 experimental group students and 29 control group students. The method of data collection is done by test. Data analysis used parametric statistics with t-test (independent sample t-test) with SPSS for windows version 25.0. The results showed that the Realistic Mathematics Education learning approach had a positive effect on improving mathematics learning outcomes. This is evidenced by the results of the independent sample t-test analysis with a significance value of 0.000 <0.05. Based on the analysis and discussion, there are differences in the final average increase in mathematics learning outcomes, namely the experimental group of 83.45 and the control group of 72.24. The results of the study can be concluded that the use of realistic mathematics education learning approach has a positive effect on improving mathematics learning outcomes.